CRITICAL REVIEW ON THE ROLE OF PHYSICAL THERAPY TECHNICIANS IN IMPROVING PATIENT OUTCOMES AND SATISFACTION. - Saleh nasser muhammad Alkhamsan, Bader Ali Saleh Almahamed, Hamad Mana Saleh Al Mutarid, Mohammed Saleh Mohammed Al khamsan, Mohammed Salem Hadi Alyami, Salem Mohammed Saleh ALKhomsan, Saleh Mane Saleh Almotared, Mahdi Salem Habban Alzulaiq (Chelonian Research Foundation, 2023)
This critical review investigates the essential part of physical therapy suppliers in making strides in understanding results and satisfaction. A subjective literature survey was conducted by analyzing the strategies utilized, and the results came from different thoughts. The examination incorporated visual maps, charts, and tables to outline the discoveries. The session investigates the effect of physical specialist administrations on healthcare and highlights their significance in differing populations. The review concludes with proposals for progressing the utilization of biological therapy in clinical settings. These proposals center on advancing scholarly programs, supporting collaborative organizations, and supporting evidence-based practices. Keywords: Physical therapy, rehabilitation, patient outcomes, satisfaction, healthcare, technician roles, evidence-based practice.